Another Way Home : a Chicory Inn Novel - Raney, Deborah (Thorndike, Maine : Center Point Large Print, 2015)
"The Whitmans are adding grandchildren to their family, but middle daughter, Danae, is childless. Though Danae is ready to consider adoption, her husband will not discuss it. Volunteering at a women's shelter is teaching Danae to live her life with gratitude, but then heart-wrenching events on Thanksgiving weekend threatens turmoil for the entire Whitman clan"--
Keywords: Large type books; Domestic fiction; Christian fiction